Outcome of Implantable Cardioverter Defibrillator in a Patient with Bradycardia due to Third-Degree AV Block after Electrical Shock: 8-year follow-up - Si Dung Chu; Linh Tran Pham; Giang Song Tran; Khanh Quoc Pham; Minh Thi Tran; Thu Kim Thi Tran; Huy Quang Doan (International Journal of Medical Toxicology and Legal Medicine, 2024)
Cardiac arrhythmias due to electrical shock are rare in emergency admissions. We report a case of a 61-year-old male patient who was admitted to the emergency room for fainting after electric shock, presenting with bradycardia and third-degree AV block, and multiple episodes of Torsades de pointes ventricular tachycardia; This is a very dangerous cardiac complication that can easily lead to ventricular fibrillation and cardiac arrest. The patient was promptly detected and treated with electrical cardioversion to terminate Torsades de pointes ventricular tachycardia, resuscitation, temporary Pacemaker Implantation, and coronary artery examination. He then underwent Implantable Cardioverter Defibrillator (ICD) and has been followed up and managed for over 8 years. Currently, the ICD is functioning well, and his health is stable. Complications from electrical shock injuries need to be detected early for timely resuscitation and emergency treatment, especially for dangerous arrhythmias. Patients require long-term follow-up, treatment, and management of potential late complications.